First-Line Helicobacter pylori Eradication in Patients with Chronic Kidney Diseases in Taiwan. (11th December 2017) - Liang, Chih-Ming; Chiu, Chien-Hua; Wang, Hsing-Ming; Tai, Wei-Chen; Yao, Chih-Chien; Tsai, Cheng-En; Kuo, Chung-Mou; Chiu, Yi-Chun; Wu, Keng-Liang; Lee, Chen-Hsiang; Tsai, Kai-Lung; Huang, Chih-Fang; et al.
Abstract : Aims . Patients with chronic kidney disease (CKD) and Helicobacter pylori ( H. pylori ) infection have a higher incidence of gastroduodenal diseases and therefore are recommended to receive eradication therapies. This study aimed to assess the efficacy of a 7-day standard triple therapy in patients with CKD (eGFR < 60 ml/min/1.73 m 2 ) and to investigate the clinical factors influencing the success of eradication. Methods . A total of 758 patients with H. pylori infection receiving a 7-day standard first-line triple therapy between January 1, 2013, and December 31, 2014, were recruited. Patients were divided into two groups: CKD group (N = 13 0 ) and non-CKD group (N = 628 ). Results . The eradication rates attained by the CKD and non-CKD groups were 85.4% and 85.7%, respectively, in the per-protocol analysis (p = 0 . 933 ). The eradication rate in CKD stage 3 was 84.5% (82/97), in stage 4 was 88.2% (15/17), and in those who received hemodialysis was 87.5% (14/16). There were no significant differences in the various stages of CKD (p = 0 . 982 ). The adverse events were similar between the two groups (3.1% versus 4.6%, p = 0 . 433 ). Compliance between the two groups was good (100.0% versus 99.8%, p = 0.6 49 ). There was no significant clinical factor influencing the H. pylori eradication rate in the non-CKD and CKD groups. Conclusions . This study suggests that the H. pylori eradication rate and adverse rate in patients with CKD are comparable to those of non-CKD patients.